(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2018)
The results of an investigation are presented, which involve reviewing the techniques used in the entrepreneurship center of the Minuto de Dios University Corporation to promote entrepreneurship and innovation among its postgraduate students. Subsequently, the entrepreneurship and innovation climate for these students is measured following the parameters of the Global Entrepreneurship Monitor, thereby highlighting the main needs of the center. The aim is to propose improvement strategies to contribute significantly to the progress of entrepreneurship within the institution and thus strengthen the entrepreneurial spirit among postgraduate students.